Survivors and colonizers: Contrasting biogeographic histories reconciled in the Antarctic freshwater copepod Boeckella poppei - Maturana, Claudia S.; Biersma, Elisabeth M.; Díaz, Angie; González-Wevar, Claudio; Contador, Tamara; Convey, Peter; Jackson, Jennifer A.; Poulin, Elie (Frontiers in Ecology and Evolution, 2022)
Two main hypotheses have been proposed to explain the contemporary distribution of Antarctic terrestrial biota. We assess whether the current distribution of maritime Antarctic populations of the freshwater copepod Boeckella poppei is the result of (1) a post-Last Glacial Maximum (LGM) colonization, or whether (2) the species survived in regional glacial refugia throughout the LGM and earlier glaciations. Using 438 specimens from 34 different sampling sites across Southern South America, South Georgia, South Orkney Islands, South Shetland Islands and the Antarctic Peninsula, we analysed mitochondrial and nuclear sequences to uncover patterns of genetic diversity and population structure. We also performed median-joining haplotype network, phylogenetic reconstruction and divergence time analyses. Finally, we evaluated past demographic changes and historical scenarios using the Approximate Bayesian Computation (ABC) method. Our data support the existence of two clades with different and contrasting biogeographic histories. The first clade has been present in maritime Antarctica since at least the mid-Pleistocene, with the South Orkney Islands the most likely refugial area. The second clade has a broader distribution including southern South America, South Georgia, South Shetland Islands and the Antarctic Peninsula. The ABC method identified long-distance dispersal (LDD) colonization event(s) from southern South America to South Georgia and the maritime Antarctic after the LGM deglaciation, supporting more recent colonization of Antarctic locations. The current Antarctic and sub-Antarctic distribution of B. poppei is likely derived from two independent biogeographic events. The combination of both (1) post-LGM colonization from southern South America and (2) longer-term persistence in in situ regional refugia throughout glacial periods challenges current understanding of the biogeographic history of Antarctic freshwater biota. Re-colonization of ice-impacted Antarctic areas would have occurred following a LDD and Establishment model, pointing to the existence of possible post-dispersal barriers, despite widely assumed high passive dispersal capacity in freshwater invertebrates.